Quantitative analysis of some enzymes and metabolites involved in energy metabolism of Cock spermatozoa and their fractions - GEHLAUT, B S; MANGLE, N S; DATTA, I C; YADAV, R S (The Indian Journal of Animal Reproduction, 2023)
To ensure a better insight into the sperm metabolism in cock spermatozoa, an attempt was made to study variousbiochemical parameters in the whole spermatozoa and their fractions. Two glucose metabolites, pyruvate and lactate werestudied to find out the status of their metabolism in the head and tail fractions of spermatozoa. Out of2 gluconeogenic enzymes,glucose-6-phosphatase and fructose-I, 6-bisphosphatase, the latter was only in traces in the head fraction whereas the formerwas upto the extent of 12% in the head. Two citric acid cycle enzymes, malate dehydrogenase and fumarase were found almostidentical in activity in the head and tail fractions out of which about 5% activity was found in the head fraction which may be dueto contamination from the tail fraction. Out of 3 phosphatases, adenosine triphosphatase, acid phospahatase and alkalinephosphatase, the last showed minimum activity in the head and tail fractions of spermatozoa of White Leghorns.
Keywords: Biochemical parameters; spermatozoa! fractions; cocks